FORMAL METHODS ADAPTATION IN PAKISTAN’S SOFTWARE INDUSTRY - Osama, S.; Iqbal, S.; Ahsan, A. (The Nucleus, 2012)
This study has been done to understand the current usage pattern of formal methods in the software industry of Pakistan. The objectives of the study was to ascertain if organizations are using formal methods, what kinds of organizations are using them and what are the challenges associated with their usage. The study is exploratory as very limited literature on formal methods in Pakistan is available. The study employs literature reviews to understand the global trends in formal methods. As per the primary research, there is currently no organizations or projects utilizing formal methods in Pakistan. Key inhibitors in the adaptation of formal methods are also explored and highlighted through the study. As a conclusion to the study, a set of recommendations are delivered for promoting the use of formal methods in Pakistan focusing on regulatory support, academic development and methods to promote the usage in public and private sector